MGMP BIOLOGI DAN BAHASA INDONESIA SMA/MA MENGATASI PERMASALAHAN UNTUK PENCARIAN BUKTI EMPIRIS BENTUK SOAL YANG DIUJIKAN DI SEKOLAH - Subali, Bambang; Suyata, Pujiati (Universitas Negeri Yogyakarta, 2015)
The ibM community service aims at training the MGMP teachers ofbiology & indonesian language subject in yogyakarta municipality and slemanregency in order to have ability to develop test which is composed of divergentand convergent test items. Also, the teachers are able to perform qualitative andquantitative analysis to the developed items. To meet the targets, this community service was conducted using lecturing;questioning and answering; and practicing techniques. With regard tothis,the practicing technique include: (1) writing test items, (2) performing deepunderstanding to the quality of test items qualitatively, and (3) analyzing itemsusing Quest program.Then,the researches guided the teachers throgh email todevelop a test which were used in their schools. The last activity was analysingtheir data using Quest program. The findings of this activity, the teachers had succesfully produced ablue print and a set of sample items both divergent and convergent model andit was review between the participants. After each participants conducted of thetest administration on each school, the result of the Quest analysis showed thatsome items of the test was conducted by 21 MGMP teachers of biology subject& 16 MGMP teachers of indonesian language subject didn